Seasonal variability of ionic concentrations in surface snow and elution processes in snow–firn packs at the PGPI site on Ürümqi glacier No. 1, eastern Tien Shan, China - Li, Z.; Edwards, Peter; Mosley-Thompson, E.; Wang, F.; Dong, Z.; You, X.; Li, H.; Li, C.; Zhu, Y. (International Glaciological Society, 2006)
To investigate the effects of both non-meltwater and meltwater-related post-depositional processes on chemical species within the snow–firn pack, a research program, the Program for Glacier Processes Investigation, was initiated in July 2002 by the Tien Shan Glaciological Station, Chinese Academy of Sciences. The seasonal variability of the ionic concentrations in surface snow samples and ion elution behavior in the snow–firn pack were assessed from surface samples collected year-round and 1011 samples collected from a snow pit at weekly intervals from September 2003 through September 2004. The results indicate that elevated ionic concentrations in spring and summer result from Asian dust-storm-derived aerosol input and other aerosols entrained in precipitation. Potential sources of these chemical species are explored using correlation and factor analyses. The elution sequence through the snow–firn pack was determined to be SO42− > Ca2+ > Na+ > NO3− > Cl− > K+ > Mg2+ > NH4+. The elution of ions at the sampling site was found to be driven primarily by air temperature and became evident when a diurnal mean temperature of −3.6°C was attained. At 0.3°C all of the year-round new ionic input was leached from the snow.